1964
DOI: 10.1104/pp.39.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Sugars by Plant Tissues

Abstract: There is already evidence that processes other than simple diffusion contribute to the uptake of sugars by some plant cells. For example, the preferential absorption of particular sugars by Scenedesmus (21,22), Peltigera (12), and tomato roots (8), and the effects of metabolic inhibitors on uptake (5,11,15) are well established. Moreover, accumulation against apparent concentration gradients has been shown for sugar cane tissue (4) and the ability of carrot tissues, rich in sugar, to take up all of the glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
25
1

Year Published

1966
1966
1985
1985

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 14 publications
1
25
1
Order By: Relevance
“…In botlh carrot root anid corn root tissue L-arabinose and D-ribose are accumiulated as such (8). In bean endocarp L-arabinose and D-ribose (table V) do not inhibit fructose uptake over a vide range of concentratioins.…”
mentioning
confidence: 95%
“…In botlh carrot root anid corn root tissue L-arabinose and D-ribose are accumiulated as such (8). In bean endocarp L-arabinose and D-ribose (table V) do not inhibit fructose uptake over a vide range of concentratioins.…”
mentioning
confidence: 95%
“…Grant and Beevers describe an absorption process which is putatively a smooth hyperbolic function of concentration with an apparent Km of approximately 10 mm. Laties, on the other hand, finds uptake to be virtually zero-order at concentrations approaching 10 yM. Both studies report uptake against a gross concentration 'The work herein generously was supported by a grant from the United States Atomic Energy Commission.…”
mentioning
confidence: 97%
“…Significant questions which persist regarding the process of glucose absorption in higher plant tissues are best revealed by a comparison of the observations of Grant and Beevers (10) on glucose absorption by carrot slices and of Laties (15) on glucose uptake by potato discs. Grant and Beevers describe an absorption process which is putatively a smooth hyperbolic function of concentration with an apparent Km of approximately 10 mm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reciprocal inhibition studies strongly support the conclusion that o-glucose, D-galactose, and D-mannose are taken up by the same system. Previously, Grant and Beevers (10) reported that uptake of galactose by carrot slices and corn root tips was inhibited by glucose, but that uptake of glucose was not inhibited by galactose. For immature internodal tissue of sugarcane, Bowen (2) found mutual inhibition between galactose and glucose, and the K, for galactose agreed closely with its Km.…”
mentioning
confidence: 99%